Latitudinal Variation in Trematode Prevalence Across Regions in North and South America: Evidence of an Inverse Gradient in Second‐Intermediate and Final Hosts - Christopher Moore; Krista McCoy; Michael McCoy (Journal of Biogeography, 2026)
Aim We tested whether the inverse latitudinal diversity gradient (LDG) observed for trematode parasites in first‐intermediate snail hosts extends to second‐intermediate and definitive host taxa. Location Sub‐tropical to temperate latitudinal zones (±23°–47.6°) in North and South America. Taxon Trematode parasites (Class: Digenea); crustacean second‐intermediate hosts (Infra‐order: Brachyura; Anomura); fish second‐intermediate hosts (Class: Actinopterygii); and fish final hosts (Class: Actinopterygii). Methods Using meta‐analysis, we reviewed and synthesised existing evidence on trematode prevalence across latitudes, focusing on studies that reported these parasites in intertidal species of crustaceans and cryptobenthic fishes. We evaluated whether infection prevalence at the second‐intermediate and final host stages followed an inverse LDG. Results Evidence indicates that trematode prevalence in second‐intermediate and definitive hosts is greater at higher latitudes, consistent with an inverse LDG. This is counter to expectations given the higher diversity of potential hosts near the equator. Main Conclusions Trematode parasites may exhibit an inverse LDG due to temperature‐dependent coevolutionary dynamics. At lower latitudes, higher temperatures likely increase parasite virulence, leading to greater parasite‐induced mortality and reduced parasite persistence. More research is needed that quantifies trematode prevalence in the same hosts from tropical to temperate latitudinal zones, as broader biogeographic studies would offer insight into Red Queen dynamics.